Analysis of Business Feasibility Study in the Development of Tofu and Tempe Business UMKM in Pondok Jeruk Village Reviewed from the Financial Aspect - Refani Nafi Sara; Abdur Rohman (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
This research aims to determine the business feasibility of the Tofu and Tempe Business in Pondok Jeruk Village, to determine the feasibility from the financial aspect. This research uses quantitative research methods. The analytical tool used for this financial aspect uses Payback Period (PP), Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI) analysis, to determine whether a business is feasible or not. The results of the analysis from the financial aspect show that this Tofu and Tempe Business is said to be feasible with a project life of 10 years at a discount rate of 10%.  Analysis of the eligibility criteria resulted in a Payback Period (PP) of 8 months 7 weeks, a Net Present Value (NPV) of IDR 137,689,184, a Profitability Index (PI) value of 1.14% and an Internal Rate of Return (IRR) of 32%.